Pengaruh Kompetensi Terhadap Kinerja Pegawai Pada Dinas Kearsipan Dan Perpustakaan Kabupaten Badung Provinsi Bali - Rahayu, Ni Made Anjaswari; Winaya, I Ketut; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
In addition to media information is also evidence that can be justified. Archives are products created by any agency for their daily activities that underlie taking action, carrying out daily activities, and organizational memory. The number of samples used were 38 people from employees and the public who were taken by accidental sampling. Data collection using a questionnaire. technique The data analysis technique used simple linear regression analysis, and got the result Y = 29,156+ 2,395X1. The positive coefficient of competence is 2.395, meaning that if the employee's competence increases, the employee's performance will increase. Competence has a positive and significant effect on the performance of the Badung Regency Archives and Library Office employees. 60.2% is the magnitude of the influence of competence on the performance of the employees of the Archives and Library Office of Badung Regency. Keywords: competence, performance, employees